Optimizing Work Performance - Fahruzi Ritonga, Dadang; Isa Indrawan, Muhammad (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
Employees are not just resources, but rather capital or assets for institutions or organizations. Because of this, a new term emerged outside of human resources, namely human capital. Here human resources are seen not just as the main asset, but an asset that is valuable and can be multiplied, developed (compared with an investment portfolio) and not vice versa as a liability (expense). Here the perspective of human resources as an investment for institutions or organizations is more prominent. The results of this research are as follows: Organizational Culture has a positive and significant effect on Organizational Commitment with a value of 0.518 and a significant value of 0.000. Organizational Culture has a positive and significant effect on Work Performance with a value of 0.195 and a significant value of 0.035. Organizational Commitment has a positive and significant effect on Job Performance with a value of 0.554 and a significant 0.000. Job Stress has a negative and significant effect on Organizational Commitment with a value of -0.412 and a significant value of 0.000. Job Stress has a negative and significant effect on Job Performance with a value of -0.211 and a significant value of 0.036. Organizational culture has a positive and significant effect on work performance through organizational commitment with a value of 0.287 and a significant value of 0.000. Job Stress has a negative and significant effect on Job Performance through Organizational Commitment with a value of -0.228 and a significant value of 0.001.